PENGARUH DOSIS PUPUK KANDANG SAPI TERHADAP SIFAT FISIK DAN KIMIA TANAH PADA TANAMAN KACANG TANAH (Arachis Hypogaea L.) - Viktor Wawo (Agriculture Faculty of Flores University, 2018)
The Effect of Dosage Organik Fertilizer on Physical Properties and Land Chemistry in Soan Beans (Arachis Hypogaea L.). This Research Aims To: Determine The Effect Of Cow Manure Does On Soil Physical Properties Of Peanut Plants. Knowing The Effect Of Cow Manure Does On Soil Chemical Properties In Peanut Plants. To Know Optimum Dose Of Cow Manure Can Affect Physical And Chemical Properties Of Soil Peanut Plant. The treatments used in this study were Pk0 (0 Ton Ha-1 or without Cow Manure), Pk1 (10 Ton Ha-1 Cow Manure), Pk2 (20 Ton Ha-1 Cow Manure), Pk3 (30 Ton Ha- 1 Cow Manure, Pk4 (40 Ton Ha-1 Cow Manure). The Observing Variables in This Study are Soil Physical Properties Variables, which include Bulk Density (G Cm-3) and Total Soil Pore Space (%), And Soil Chemical Properties Variables That Cover N-Total Soil, P-Soil Available, K-Available Soil, C-Organic Soil, And Ph Soil. Research Results Show That Giving Cow Cage Fertilizer in Peanut Plants In General Has an Effect of Improving Soil Physical Properties in the Form of Increasing Soil Volume Weight and Total Soil Pore Space, Giving Cow Cage Fertilizer in Peanut Plants Generally Affecting Improving Soil Chemical Properties in the Form of Increasing N-Total , P-Available, K-Available, C-Organic And Soil Ph As Well As The Optimum Dose Of Cow Manure That Can Improve The Physical And Chemical Properties Of Soil In The Best Peanut Plants Are 40 Tons / Ha.